A preliminary evaluation study of new generation multiplex STR kits comprising of the CODIS core loci and the European Standard Set loci. (November 2017) - Tan, Jolena Ying Ying; Tan, Yuen Peng; Ng, Shilen; Tay, Annabel Suan; Phua, Yong Han; Tan, Wei Jie; Ong, Terenze Yao Rui; Chua, Li Min; Syn, Christopher Kiu Choong
Abstract: The GlobalFiler™ (Life Technologies), Investigator ® 24plex QS (Qiagen), and PowerPlex ® Fusion 6C (Promega) kits are the latest generation 6-dye fluorescent chemistry STR-PCR amplification kits. These kits allow for the simultaneous amplification of the CODIS core loci and the European Standard Set loci, as well as a few Y-STR loci in addition to the standard sex-determining marker Amelogenin. The present study was designed to be a preliminary evaluation of the three STR-PCR kits in terms of sensitivity, profile recovery from degraded DNA samples, tolerance to PCR inhibitors, and detection of minor components in DNA mixtures. The results showed that the three STR-PCR kits had relatively similar performance with each kit faring better for the different aspects studied. The PowerPlex ® Fusion 6C and the Investigator ® 24plex QS kits were shown to tolerate inhibitors better, while the GlobalFiler™ kit appeared to have a higher mean percentage recovery of alleles from low template DNA samples and for minor components in DNA mixtures. Highlights: GlobalFiler™, Investigator ® 24plex QS and PowerPlex ® Fusion 6C kits were evaluated. Robust amplifications and concordant STR results were obtained by all three kits. Peak height balance was well above 60% at 31 pg DNA template for all three kits. Effects of DNA degradation and PCR inhibition were also well tolerated.